Economic impact of climate change on maize productivity in Northern Nigeria - Ibrahim, Kasimu (2015)
In recent years, climate change has become a more serious issue than any other environmental problem. One of the main concerns is the risk it poses to food production, especially in developing countries, where a large percentage of the population relied heavily on agriculture for survival. Irrational allocation of resources also contributed to the decline of agricultural productivity in Africa. In Nigeria, few researches focused on assessing the economic impact of climate change and ways of improving productive efficiency of maize. Having established these problems, the main goals of this study are to estimate the economic impact of climate change on net revenue from maize in northern Nigeria and also to identify the role of socioeconomic factors in cushioning the impact. Furthermore, this research aimed to measure the technical efficiency of maize production and identify its determinants. As part of solution to the problems results of the study are intended to inform farmers, researchers and policy makers, on the economic impact of climate change on net revenue and technical efficiency of the respondents in the study area. Climate data for the study mainly includes temperature and rainfall. Data on net revenue, input use, cost of production, yield and farm specific factors were collected through respondent’s survey. The main methodologies used in the analysis of the study are the Ricardian and the stochastic frontier approaches. Results of the study obtained through Mann-Kendall, Ricardian, stochastic frontier and Tobit analyses revealed evidence of climate change. Although the impact was mixed, temperature played a more important role in determining farm net revenue, as against rainfall during the crop growing season. Furthermore, market distance, farm size and farm power were the factors that significantly determined net revenue. On the technical efficiency of farms, the inputs tested were found to significantly increase maize productivity. Findings showed that education, credit, household size, age and gender contributed significantly in reducing technical inefficiency of the respondents. The conclusion of the study was that climate change had a mix impact on revenue from maize production. In addition, certain socioeconomic factors could be used by farms to adapt to climate change. Projections based on the analyses of the study showed that future climate change will be harmful to net revenue. Although the respondents achieved high level of technical efficiency findings of the study revealed that technical inefficiency exist among maize farms. All inputs tested could be used to increase productivity, but increase in the supply of labor may lead to a more significant rise in productivity. Similarly, factors such as education, credit, age, household size and gender could be explored to improve technical efficiency. To comprehensively address the problems of climate change and inefficient resource use, there is the need to focus attention on assessing the impacts of climate change and technical efficiency, two problems that previous studies have not addressed properly. The policy implications of these results, if carefully evaluated are expected to serve as a framework for developing climate change adaptation and efficient resource utilization options in the study area.